1988
DOI: 10.2337/diacare.11.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Role and Management of Exercise in Diabetes Mellitus

Abstract: As more is understood about the physiology of exercise, in both normal and diabetic subjects, its role in the treatment of diabetes is becoming better defined. Whereas people with diabetes may derive many benefits from regular physical exercise, there are also several hazards that make exercise difficult to manage. In type I (insulin-dependent) diabetes, there are risks of hypoglycemia during or after exercise or of worsening metabolic control if insulin deficiency is present. Type II (non-insulin-dependent) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 50 publications
(66 reference statements)
1
56
1
1
Order By: Relevance
“…However, there was a tendency towards greater decline with higher pre-walk blood glucose levels (Table II). DISCUSSION Regular intensive exercise in diabetes care is known to induce an immediate lowering of blood glucose levels, increased insulin sensitivity, and a decline of glycated haemoglobin (HbA1c) (8). The results from this study show that low-intensity exercise was sufcient to produce a signi cant acute reduction of blood glucose levels in elderly type 2 diabetes patients.…”
Section: Resultsmentioning
confidence: 54%
“…However, there was a tendency towards greater decline with higher pre-walk blood glucose levels (Table II). DISCUSSION Regular intensive exercise in diabetes care is known to induce an immediate lowering of blood glucose levels, increased insulin sensitivity, and a decline of glycated haemoglobin (HbA1c) (8). The results from this study show that low-intensity exercise was sufcient to produce a signi cant acute reduction of blood glucose levels in elderly type 2 diabetes patients.…”
Section: Resultsmentioning
confidence: 54%
“…The blood glucose lowering effect of exercise is largely due to the cumulative effects of single exercise bouts [4,6,7,9]. The interaction between glycaemic control and aerobic capacity may, however, be more complex because it has been suggested that lowered VO2 at in diabetic subjects is due to a high HbA~ level through increased oxygen affinity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have previously suggested that exercise improves serum lipid profile in Type 2 diabetes [10][11][12]. However, it has been speculated that the most important impact of exercise in Type 2 diabetes is the beneficial effect on cardiovascular risk factors [6,8]. Recently, a study on obese healthy subjects showed that combined diet and exercise training resulted in a significantly higher increase in HDLcholesterol than diet alone [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that regular physical activity improves quality of life, reduces the risk of mortality from all causes (1)(2)(3)(4), and is particularly advantageous in subjects with impaired glucose tolerance (5,6) or type 2 diabetes (7)(8)(9)(10)(11)(12). Physical activity counseling can motivate most diabetic subjects to increase their levels of voluntary energy expenditure (9 -11), but, at present, the relationship between amounts of physical activity and longterm beneficial effects in type 2 diabetes care is unknown.…”
mentioning
confidence: 99%